(untitled) (Agricultural Engineering, 2023)
This study aims to determine and evaluate the operating parameters of three modern self-propelled forage harvesters during maize silage harvest. The machines were equipped with operator assistance systems. Field tests were conducted for three self-propelled forage harvesters: Claas Jaguar 870, Claas Jaguar 950, KroneBiG X 650. The tests were conducted in large-scale farms located in Wielkopolskie and Pomorskie voivodeships. Maize was harvested at the beginning of the full-grain maturity stage. A complete time study covering four control shifts in accordance with BN-76/9195-01 was performed to determine operating ratios and indicators. Fuel consumption was determined using the full tank method. The Claas Jaguar 950 forage harvester had the highest effective mass performance: 141.3 Mg·h-1. The same machine also achieved the lowest fuel consumption per tonne of fresh matter (FM) harvested: 0.51 kg·Mg-1. Labour expenditure for the self-propelled forage harvesters tested during the total time of change ranged from 0.38 to 0.62 labour hour per hectare. The tested machines also had very high technical and technological reliability.